2011
DOI: 10.1111/j.1471-0528.2011.03089.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes using LigaSure compared with conventional bipolar instruments in laparoscopic hysterectomy: a randomised controlled trial

Abstract: Objective To compare the effects of LigaSure versus the conventional bipolar technique on operating time and blood loss during laparoscopic hysterectomy.Design A randomised controlled trial.Setting Three teaching hospitals.Population Women undergoing a laparoscopic hysterectomy for benign indications.Methods 140 women undergoing a laparoscopic hysterectomy were randomised for LigaSure or conventional bipolar instruments.Main outcome measures Primary outcome was operating time from initial skin incision till de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 33 publications
(62 reference statements)
1
47
0
Order By: Relevance
“…However, more than 97% of the notes were generated electronically, which decreases loss of data owing to illegibility of handwritten notes, and the notes included questions evaluating preoperative and postoperative extremity symptoms. It is also reassuring that the rate of other complications is similar to the rates reported in prospective studies (randomized trials) of gynecologic laparoscopic surgery . The description of complications is strengthened by our use of the Clavien–Dindo classification…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, more than 97% of the notes were generated electronically, which decreases loss of data owing to illegibility of handwritten notes, and the notes included questions evaluating preoperative and postoperative extremity symptoms. It is also reassuring that the rate of other complications is similar to the rates reported in prospective studies (randomized trials) of gynecologic laparoscopic surgery . The description of complications is strengthened by our use of the Clavien–Dindo classification…”
Section: Discussionsupporting
confidence: 60%
“…It is also reassuring that the rate of other complications is similar to the rates reported in prospective studies (randomized trials) of gynecologic laparoscopic surgery. [5][6][7][8] The description of complications is strengthened by our use of the Clavien-Dindo classification. 4…”
Section: Discussionmentioning
confidence: 99%
“…McCareken et al [11] reported more blood loss in VH group compared to AH and laparoscopic-assisted VH (LAVH) in their study. Janssen et al [12] found that the blood loss was lower in TLH using EBVS as compared to conventional bipolar TLH.…”
Section: Discussionmentioning
confidence: 98%
“…The reduction in blood loss with the LigaSure in those studies may be explained by the less effective hemostasis in large vessels by ultrasonic devices [25][26][27]. One other study that compared LigaSure with conventional bipolar instruments in a random way in laparoscopic hysterectomy was also not able to detect any significant differences with respect to operating time or blood loss [28].…”
Section: Discussionmentioning
confidence: 94%